Penguatan Wellness Tourism Melalui Pengolahan Produk Pertanian di Desa Bermi - Suharno, Novianto Edi; Aly, M. Nilzam; Prihatiningsih, Septyani; Siswantoro, Pulung; Putri, Rahma Fadiya; Auliyak, Shulton; Yuliyanto, Adhi; Sinaga, Guanter Hatoguan (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
Wellness tourism is defined as a type of tourism that aims to improve the quality of health and fitness through physical, psychological, spiritual, and mental activities. Bermi Village, Probolinggo have great potential to support the development of wellness tourism. The problems that occur are: (1) The people are not aware of the potential of wellness tourism in their area; (2) The Horticulture of agricultural products are not processed into products that have more value; (3) and the role of Badan Usaha Milik Desa (BUMDES) in supporting the tourism sector has not been optimized. As a first step to reduce these problems, the community service team conducted socialization on wellness tourism management and training on processing local agricultural products into healthy products which were attended by 30 participants. The activity results showed that the community was enthusiastic about participating in the program and knowledge about wellness tourism increased.